E-Magazine Berbasis Discovery Learning Terintegrasi Ayat Al-Qur’an: Pengembangan Media Pembelajaran Biologi pada Sistem Pernapasan - Afifa Zahra Simanungkalit; Miza Nina Adlini (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study aims to develop a learning medium in the form of an e-magazine based on Discovery Learning integrated with Qur’anic verses, as well as to examine its validity, practicality, and effectiveness in improving students’ learning outcomes on the respiratory system material for Grade XI. The method used was Research and Development (R&D) with the ADDIE model. The instruments used in this study included interview sheets and questionnaires. The results showed that validation by material, media, and Qur’anic integration experts indicated that the e-magazine was in the “very valid” category for use in learning, with a score of 97%. Students’ responses to the medium were categorized as “very practical” with a score of 91%, as were teachers’ responses with a score of 97%. Effectiveness testing showed an N-Gain value of 0.65, which falls into the “medium” category (moderately effective), indicating an improvement in learning outcomes after using the medium. In conclusion, this e-magazine is considered feasible and moderately effective for use as a biology learning medium, not only strengthening conceptual understanding but also instilling spiritual values through the integration of Qur’anic verses. Keywords: ADDIE, Qur’anic Verses, Discovery Learning, E-magazine